2014
DOI: 10.1371/journal.ppat.1004047
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Fate and Involvement of Infected Cells in the Induction of CD4+ and CD8+ T Cell Responses to Toxoplasma gondii

Abstract: During infection with the intracellular parasite Toxoplasma gondii, the presentation of parasite-derived antigens to CD4+ and CD8+ T cells is essential for long-term resistance to this pathogen. Fundamental questions remain regarding the roles of phagocytosis and active invasion in the events that lead to the processing and presentation of parasite antigens. To understand the most proximal events in this process, an attenuated non-replicating strain of T. gondii (the cpsII strain) was combined with a cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
97
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 92 publications
3
97
0
1
Order By: Relevance
“…Furthermore, phagocytosis of CPS by myeloid cells elicited surprisingly insignificant CD4 ϩ and CD8 ϩ T cell responses and ineffective immunity to Toxoplasma (21). In contrast, active invasion of myeloid cells by CPS triggered potent CD4 ϩ and CD8 ϩ T cell responses and highly effective protective immunity to Toxoplasma (21).…”
Section: Myd88mentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, phagocytosis of CPS by myeloid cells elicited surprisingly insignificant CD4 ϩ and CD8 ϩ T cell responses and ineffective immunity to Toxoplasma (21). In contrast, active invasion of myeloid cells by CPS triggered potent CD4 ϩ and CD8 ϩ T cell responses and highly effective protective immunity to Toxoplasma (21).…”
Section: Myd88mentioning
confidence: 98%
“…Recent studies using the CPS vaccination model have found a role for active parasite invasion in the activation of myeloid cells and the priming of CD4 ϩ and CD8 ϩ T cell immunity (30)(31)(32). Furthermore, phagocytosis of CPS by myeloid cells elicited surprisingly insignificant CD4 ϩ and CD8 ϩ T cell responses and ineffective immunity to Toxoplasma (21). In contrast, active invasion of myeloid cells by CPS triggered potent CD4 ϩ and CD8 ϩ T cell responses and highly effective protective immunity to Toxoplasma (21).…”
Section: Myd88mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite limited access, the CNS is inundated by immune cells from the periphery during the chronic stage of T. gondii infection. The adaptive immune responses in the CNS have been extensively investigated, describing an important contribution to the local parasite control (22)(23)(24)(25). Besides, several studies have highlighted the function and phenotype of certain mononuclear cells such as microglia, brain DCs, and macrophages upon cerebral toxoplasmosis; however, the role of recruited newly described myeloid cell subpopulations remains undefined (19,26,27).…”
mentioning
confidence: 99%